2011
DOI: 10.1111/j.1439-0426.2011.01671.x
|View full text |Cite
|
Sign up to set email alerts
|

Winter coastal movement of Gulf of Mexico sturgeon throughout northwest Florida and southeast Alabama

Abstract: Summary In order to characterize distribution of Gulf of Mexico sturgeon in nearshore Gulf of Mexico (GOM) and compare distributions prior to and after hurricane activity, 187 Gulf sturgeon (Acipenser oxyrinchus desotoi) were tagged with acoustic transmitters in Ochlockonee, Apalachicola, Brothers, Choctawhatchee, Yellow, Blackwater and Escambia rivers to monitor marine movement along the GOM coastline from Florida (FL) to Alabama (AL). Nine juveniles (79–86 cm fork length, 3.4–5.2 kg), 22 sub‐adults (91–126 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 18 publications
4
38
1
Order By: Relevance
“…Moreover, quantifying benthic resource distribution coupled with sediment characteristics are surrogate approaches used to identify primary sturgeon foraging areas (Fox et al 2002, Brooks & Sulak 2005, Harris et al 2005, Nellis et al 2007, Ross et al 2009). These data suggest that Gulf sturgeon, like most sturgeon, are opportunistic benthic foragers (Huff 1975, Miller 2004, Vecsei & Peterson 2004, Parauka et al 2011) as Breder (1929 showed in his detailed description of sturgeon foraging behavior. Sturgeon use barbels, snout and head electroreceptors, their specialized tubular mouth, and suction feeding (Miller 2004, Vecsei & Peterson 2004) to obtain prey from sediments.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Moreover, quantifying benthic resource distribution coupled with sediment characteristics are surrogate approaches used to identify primary sturgeon foraging areas (Fox et al 2002, Brooks & Sulak 2005, Harris et al 2005, Nellis et al 2007, Ross et al 2009). These data suggest that Gulf sturgeon, like most sturgeon, are opportunistic benthic foragers (Huff 1975, Miller 2004, Vecsei & Peterson 2004, Parauka et al 2011) as Breder (1929 showed in his detailed description of sturgeon foraging behavior. Sturgeon use barbels, snout and head electroreceptors, their specialized tubular mouth, and suction feeding (Miller 2004, Vecsei & Peterson 2004) to obtain prey from sediments.…”
Section: Introductionmentioning
confidence: 85%
“…Beta-dyne ® impregnated petroleum jelly was used on all tagging wounds. Captured Gulf sturgeon were categorized as adult (>125.0 cm FL), sub-adult (89.1− 125.0 cm FL), and juvenile (30.4− 89.0 cm FL; Parauka et al 2011). …”
Section: Gulf Sturgeon Tagging Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Most records of sturgeon stranding events occur in river systems, due to either natural seasonal water level changes, or changes caused by dams and flood diversions (Thomas et al., ). In 2004, Hurricane Ivan caused the stranding of Gulf Sturgeon in the Escambia River, Florida and nearby bays (Parauka et al., ). This, toether with our observations, suggests that Atlantic sturgeon and their close relatives may be naturally susceptible to stranding in various habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Based on telemetry studies (Erickson et al 2011;Parauka et al 2011;Oliver et al 2013), sturgeon are known to move between river systems. Therefore, a sturgeon detected in a given river system may not belong to that river's reproductive population.…”
Section: Discussionmentioning
confidence: 99%